2020
DOI: 10.21203/rs.3.rs-115644/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urine miRNA Signature as a Potential Non-invasive Diagnostic and Prognostic Biomarker in Cervical Cancer

Abstract: MicroRNAs as cancer biomarkers in serum, plasma and other body fluids are often used but analysis of miRNA in urine is limited. We investigated the expression of selected miRNAs in the paired urine, serum, cervical scrape and tumor tissue specimens from the women with cervical precancer and cancer with a view to identify if urine miRNAs could be used as reliable non-invasive biomarkers for an early diagnosis and prognosis of cervical cancer. Expression of three oncomiRs (miR-21, miR-199a, and miR-155-5p) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 51 publications
0
15
0
1
Order By: Relevance
“…Sensitivity analysis was conducted in the 8 reports of 7 included studies and two AUC reports from one study [ 74 ] were found to be outliers ( S1 Fig ). Therefore, the two reports have been dropped in the meta-analysis of AUC of studies although no significant change has been shown in the interpretation of the result.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensitivity analysis was conducted in the 8 reports of 7 included studies and two AUC reports from one study [ 74 ] were found to be outliers ( S1 Fig ). Therefore, the two reports have been dropped in the meta-analysis of AUC of studies although no significant change has been shown in the interpretation of the result.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a study revealed, in univariate Cox proportional hazards regression analysis, that there was a significant association between high microRNA-21 expression and poor overall survival of cervical cancer patients (P <0.05). However, the study revealed insignificant association in the multivariate Cox regression analysis (P <0.05) which was analyzed within the context of many clinical characteristics, including HPV infection, age at diagnosis, parity, clinical stage, marriage age, and histopathological grade [ 74 ]. Besides, a study conducted in China showed that the 5-year survival rate of patients with highly expressed microRNA-21 was lower than those of patients with lowly expressed microRNA-21 (p<0.05) [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, com o intuito de analisar se os miRNAs presentes na urina poderiam ser usados como biomarcadores confiáveis para diagnóstico e prognóstico do câncer cervical, Aftab et al (2021) concluíram que a combinação entre miR-145-5p, miR-218-5p e miR-34a-5p presentes na urina apresentou 100% de sensibilidade e 92,8% de especificidade na distinção entre pacientes controle e pacientes com câncer. Research, Society and Development, v. 11, n. 2, e25711225776, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i2.25776…”
Section: Resultsunclassified
“…Circulating miRNAs have the potential to serve as diagnostic markers of tumor progression and this has been the focus of an increasing number of studies [14,15]. For example, serum exosomal miR-1247-3p levels in patients with primary hepatic cancer are associated with the extent of lung metastasis [16].…”
Section: Introductionmentioning
confidence: 99%